Answer:
1.67 seconds
Explanation:
h(t) = − 16t^2 + 25t + 3
When it hits the ground h=0
0 = − 16t^2 + 25t + 3
Using the quadratic formula
-b ± sqrt(b^2 -4ac)
---------------------------
2a
a = -16 b=25 c =3
Substituting what we know
-25 ± sqrt(25^2 -4(-16)3)
---------------------------
2(-16)
-25 ± sqrt(625 +192)
---------------------------
2(-16)
-25 ± sqrt(817)
---------------------------
-32
-25 + sqrt(817) -25 - sqrt(817)
--------------------------- or ---------------------
-32 -32
-.112 1.67